MASKULINITAS DALAM MEDIA ONLINE: ANALISIS WACANA KRITIS DALAM KAJIAN CERAMAH USTADZ SALAF - Ahmad Abdullah Rosyid (Asosiasi dosen IDEBAHASA KEPRI, 2020)
Media is an intermediary that is widely used in conveying information, such as print media, visual media (television), and online visual media. The information contained a lot about ideology, hegemony, power, and even marginalization. The media is also very influential in affirming the concept of gender in society, one of which is YouTube's online media which is considered the most effective in disseminating information. Various kinds of accounts publish videos with various concepts, some contain games, some have vlogs, and some contain lectures. In this paper, the researcher will discuss the contents of the lecture delivered by Ustadz Khalid on gender issues, such as differences between men and women and the characteristics of a man towards women. Three shows were taken as samples and analyzed using Norman Fairclough's critical discourse theory which offers three-dimensional concepts in it; textual, discourse, and social. The results obtained were from the three videos, Ustadz Khalid tried to instill ideology in the community. This is in line with the patriarchal family system adopted by the majority of people in Indonesia.